Revitalizing Tourism: Strategies for Sustainable Growth and Development: A Critical Review - Santhosh Kumar, K; Kurian, Anoop (International Research Journal of Parroha, 2025)
This review critically examines Revitalizing Tourism: Strategies for Sustainable Growth and Development by Anjay Kumar Mishra and Shila Mishra (2024). The book gives a multifaceted exploration of tourism’s function in regional boom, mainly emphasizing Madhesh Province of Nepal and its connection with the restaurant and retail sectors. The authors discuss sustainability as a multidimensional construct that integrates monetary, environmental, and socio-cultural views. This review evaluates the book’s conceptual strength, empirical foundations, and contributions to the broader discourse on sustainable tourism. It highlights how Mishra and Mishra’s work extends existing debates on destination management, network participation, and value-chain integration, at the same time as study figuring out areas where the analysis could be deepened—particularly in strategy formulation, virtual inclusion, and policy utility. The review also connects the book’s insights to related research on corporate social responsibility (CSR), ethical leadership, and green branding, drawing upon modern literature by Kumar and others. Overall, the book makes a treasured local contribution to sustainable tourism scholarship but requires greater theoretical synthesis and policy specificity to maximise its effect.